Enhancement of offline signature verification using support vector machine - John Ullyses O. Velaroso, Sherwin Carlo R. Cruz. 4 0 16; 5 (2022)
u
Undergraduate Thesis: (Bachelor of Science in Computer Science) Pamantasan ng Lungsod ng Maynila, 2022.
Keywords: 2 -- 0; 6; 20; 20; 2